2021
DOI: 10.1101/2021.03.22.436385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NHE6-Depletion Corrects ApoE4-Mediated Synaptic Impairments and Reduces Amyloid Plaque Load

Abstract: Apolipoprotein E4 (ApoE4) is the most important and prevalent risk factor for late-onset Alzheimer’s disease (AD). The isoelectric point of ApoE4 matches the pH of the early endosome (EE), causing its delayed dissociation from ApoE receptors and hence impaired endolysosomal trafficking, disruption of synaptic homeostasis and reduced amyloid clearance. We have shown that enhancing endosomal acidification by inhibiting the EE-specific sodium-hydrogen exchanger NHE6 restores vesicular trafficking and normalizes s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 110 publications
0
8
0
Order By: Relevance
“…57 Further, NHE6 expression attenuated amyloid precursor protein processing and amyloid beta secretion in a HEK293 cell model of human amyloid precursor protein expression 62 . In contrast, conditionally depleting NHE6 in vivo post-developmentally corrected ApoE4-mediated synaptic impairments and prevented amyloid beta production in mice 69 . Thus, both decreased 69 and increased 57 NHE6 expression have been proposed as potentially therapeutic for Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…57 Further, NHE6 expression attenuated amyloid precursor protein processing and amyloid beta secretion in a HEK293 cell model of human amyloid precursor protein expression 62 . In contrast, conditionally depleting NHE6 in vivo post-developmentally corrected ApoE4-mediated synaptic impairments and prevented amyloid beta production in mice 69 . Thus, both decreased 69 and increased 57 NHE6 expression have been proposed as potentially therapeutic for Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, conditionally depleting NHE6 in vivo post-developmentally corrected ApoE4-mediated synaptic impairments and prevented amyloid beta production in mice 69 . Thus, both decreased 69 and increased 57 NHE6 expression have been proposed as potentially therapeutic for Alzheimer’s disease. ApoE4 also exacerbates tauopathies 70 , and CS is tied to 4R tauopathy 71 .…”
Section: Discussionmentioning
confidence: 90%
“…Future work could expand on our current study and examine the effects of NHE6 loss of function in other neuronal subtypes, in astrocytes and microglia, and in mixed cultures of these cells. In particular, a pronounced glial response has been reported in NHE6 KO mice and rats (Lee et al, 2021;Pohlkamp et al, 2021;Xu et al, 2017) and in CS patient brain tissue (Garbern et al, 2010). Therefore, future study of glial activation and dysfunction in the context of NHE6 loss of function will be crucial for a fuller understanding of neurodegeneration in NHE6null brains.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have linked NHE6 function in regulating endosomal pH with APOE4-induced defects in endolysosomal trafficking in neurons (Pohlkamp et al, 2021;Xian et al, 2018). These studies have led to the proposal that enhancement of acidification of endosomes via inhibition of NHE6 actually may be beneficial to reduce the negative consequences of APOE4 on trafficking and amyloid plaque deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, hyperacidification of astrocytic endosomes was observed, leading to decreased LRP1 surface expression and impaired Aβ clearance, which proved rescuable by HDAC4 inhibition. Recent evidence suggested that not only is endosomal acidification able to restore receptor trafficking and synaptic deficits but also improve Aβ clearance in brain sections from E4‐TR mice, linking Aβ‐related and unrelated pathways (Pohlkamp et al, 2021). These differences between findings could be accounted for both by cell type‐specific processes (Wong, 2020) and different model systems ( APOE overexpressing astrocyte cultures vs tissue from APOE ‐TR mice).…”
Section: Hit 5: Endosomal Trafficking Impairmentsmentioning
confidence: 99%